Public finance mechanisms for urban infrastructure: A case study of the MyCiTi BRT, Cape Town - Macauley, Ryan Manzie (School of Architecture, Planning and Geomatics, 2018)
With tight budgets and shifts in the global economy, urban infrastructure has become a critical investment municipalities are struggling to fund. Innovative land-based financing tools have emerged as a means of funding critical urban infrastructure. At times, land-based financing tools enable local municipalities to meet their spatial goals. This dissertation reports on research highlights the potential applicability of land-based financing tools in cities of the Global South, namely Cape Town. The findings show that the City of Cape Town has the necessary supportive regulatory frameworks, urban planning policies and robust market conditions to use the land-based financing tools. While harnessing land value to partially fund infrastructure is not new, this study provides hearty evidence for policy makers and practitioners who seek to transform the spatial legacy of apartheid in a tangible way.